Agreement between the Government of the United Kingdom of Great Britain and Northern Ireland and the Government of the French Republic concerning safety certification in respect of rail transport services through the Channel Fixed Link, London 23 January and Paris 8 February 2023. ([2023-04-21]) - Unknown
No abstract available